2002
DOI: 10.1021/jp013945r
|View full text |Cite
|
Sign up to set email alerts
|

On the Measurement of Positive Soret Coefficients

Abstract: In this paper, we report Soret coefficients obtained by two independent methods and for two different systems-(water-ethanol containing respectively 60.88 and 50 wt % of water). The Soret coefficient is defined by S T ) D T /D where D T is the thermal diffusion coefficient, and D is the isothermal diffusion coefficient. In the first method, D T is determined by a 5-point sampling process in a thermogravitational column and D by the well-known OEC technique (open-ended capillary). The ratio of the experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
115
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(121 citation statements)
references
References 17 publications
5
115
1
Order By: Relevance
“…The time dependence of the diffracted signal intensity is analyzed and gives the diffusion coefficient D, the thermal diffusion coefficient D T and the Soret coefficient S T . In the benchmark test it was demonstrated that the classical TDFRS method gives reliable results for organic mixtures and also the data obtained for simple aqueous systems compare well with other experimental techniques [11][12][13][14] . However, recent studies on the surfactant hexaethylene glycol monododecyl ether (C 12 E 6 ) in water with the classical TDFRS showed, that the small amount of dye added to create a temperature grating, leads to an unexpected second mode in the concentration part of the classical TDFRS signal 15,16 .…”
Section: Introductionmentioning
confidence: 56%
“…The time dependence of the diffracted signal intensity is analyzed and gives the diffusion coefficient D, the thermal diffusion coefficient D T and the Soret coefficient S T . In the benchmark test it was demonstrated that the classical TDFRS method gives reliable results for organic mixtures and also the data obtained for simple aqueous systems compare well with other experimental techniques [11][12][13][14] . However, recent studies on the surfactant hexaethylene glycol monododecyl ether (C 12 E 6 ) in water with the classical TDFRS showed, that the small amount of dye added to create a temperature grating, leads to an unexpected second mode in the concentration part of the classical TDFRS signal 15,16 .…”
Section: Introductionmentioning
confidence: 56%
“…In the recent years it was also demonstrated that the TDFRS method gives reliable results for aqueous systems and compares well with other experimental techniques 10,[13][14][15] . But recent studies on a non-ionic surfactant by the TDFRS technique showed, that the small amount of dye, which is added to convert light into heat energy, can influence the thermal diffusion behavior of the surfactant system 16,17 .…”
Section: Introductionmentioning
confidence: 60%
“…5 In the past the thermal diffusion behavior of simple fluid mixtures has been studied extensively. [6][7][8][9][10][11][12][13] Organic liquid mixtures have been used in a benchmark test, to establish reference data. 14 Recently, special focus has been on the dependence of S T on parameters such as mass and moment of inertia.…”
Section: Introductionmentioning
confidence: 99%